2021
DOI: 10.15252/emmm.202012778
|View full text |Cite
|
Sign up to set email alerts
|

Biofabricating murine and human myo‐substitutes for rapid volumetric muscle loss restoration

Abstract: The importance of skeletal muscle tissue is undoubted being the controller of several vital functions including respiration and all voluntary locomotion activities. However, its regenerative capability is limited and significant tissue loss often leads to a chronic pathologic condition known as volumetric muscle loss. Here, we propose a biofabrication approach to rapidly restore skeletal muscle mass, 3D histoarchitecture, and functionality. By recapitulating muscle anisotropic organization at the microscale le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 61 publications
0
55
0
Order By: Relevance
“…Alongside these prescient studies to resolve the limitations in large organ design, significant success has been achieved by implementing the bottom-up tissue engineering approach in the manufacturing of tissue/organ building blocks—i.e., miniaturized constructs generally having a volume up to 1 cm 3 —which exhibit histoarchitectures and functions close to the native targeted tissue/organ. For instance, researchers have recently succeeded, to some degrees, in fabricating tissue-specific building blocks by recapitulating the architectures and functions of the human liver lobules ( Ma et al, 2016 ; Gori et al, 2020 ), the dynamic microenvironment of the alveolar-capillary unit ( Huh, 2015 ), the parallel organization of myofiber bundles ( Costantini et al, 2021 ), and the primary human small intestine ( Kasendra et al, 2018 ; Shin et al, 2019 ). Despite the diversity in their structural and cellular complexity, the conjoined outcomes of these studies indicate that effective architectural guidance provides crosstalk among the cell populations and enhances the morphogenesis of the desired tissue.…”
Section: Tackling Current Biomedical Challenges With Frontier Technologiesmentioning
confidence: 99%
“…Alongside these prescient studies to resolve the limitations in large organ design, significant success has been achieved by implementing the bottom-up tissue engineering approach in the manufacturing of tissue/organ building blocks—i.e., miniaturized constructs generally having a volume up to 1 cm 3 —which exhibit histoarchitectures and functions close to the native targeted tissue/organ. For instance, researchers have recently succeeded, to some degrees, in fabricating tissue-specific building blocks by recapitulating the architectures and functions of the human liver lobules ( Ma et al, 2016 ; Gori et al, 2020 ), the dynamic microenvironment of the alveolar-capillary unit ( Huh, 2015 ), the parallel organization of myofiber bundles ( Costantini et al, 2021 ), and the primary human small intestine ( Kasendra et al, 2018 ; Shin et al, 2019 ). Despite the diversity in their structural and cellular complexity, the conjoined outcomes of these studies indicate that effective architectural guidance provides crosstalk among the cell populations and enhances the morphogenesis of the desired tissue.…”
Section: Tackling Current Biomedical Challenges With Frontier Technologiesmentioning
confidence: 99%
“…The work of Costantini and colleagues [ 1 ] revealed the potential of microfluidic-enhanced bioprinting in combination with a bioink composed of C2C12 (mouse myogenic progenitors) embedded in a PF–alginate hydrogel mix in driving proper differentiation of muscle fibers both in vitro and in vivo, with an impressive amelioration in terms of orientation and fiber organization. Moreover, very recently, the same authors [ 57 ] demonstrated the real potentiality of 3D printing technology in obtaining macroscopic myo-substitutes in vitro and in vivo, showing an astonishing functional and morphological recovery of TA VML mouse models (90% of TA muscle mass ablation) within just 3 weeks, revealing muscular tissue replenishment with new myofibers, blood vessels and nerves and promoting full TA muscle restoration in terms of strength performance. Moreover, the employed 3D printing technique turned out to be suitable for human myogenic cells.…”
Section: Preclinical Reconstructive Therapies For Vml Treatmentmentioning
confidence: 99%
“…Furthermore, the Michael-type addition reaction ( Figure 1 B) could also cause unwanted reactions between the synthetic polymer and the cysteines of cell-membrane proteins when the cells are embedded in PEG-protein hydrogel-based scaffolds. Usually, a good cell survival 3D system with encapsulated cells is obtained using a precursor hydrogel solution with a very high cell density, ranging from 2 to 5 × 10 6 cells/mL and in some cases 3 × 10 7 cells/mL [ 23 , 24 , 25 , 26 ]. This cellular density is very far from the cellular density used for cell growth on a plate.…”
Section: Introductionmentioning
confidence: 99%
“…In this hydrogel, the fibrinogen biofunctionality and the structural versatility of the PEG molecules are combined and the stiffness can be easily modulated by increasing the cross-linking density. Therefore, it represents a good model of a photo-polymerizable hydrogel due to its prevalence in tissue engineering applications and because of its potential as a bio-ink in 3D bioprinting [ 26 , 50 ].…”
Section: Introductionmentioning
confidence: 99%